Dating apps and face-to-face meetings: the quality of relationship among online and offline couples - Chai, Pau Pau Dakkshina; Chew, Yi Erng; Hwang, Jia Yi; Lee, Po Ee; Sherwina Deepa, Devanbu (2022)
As technology is getting advanced, online dating becomes a popular way for people to develop a new relationship. Dating apps are one of the methods and have been widely accepted by people, especially the youth when they want to find a long-term partner. Dating apps provide them a platform to find their prefered partner, especially providing the minority included gay and lesbian to have more opportunities to get their ideal partner. Romantic relationship is the most common relationship that dating apps users are trying to seek for. They are not only wanting to look for a romantic relationship, but also wanting to look for a quality in the relationship. However, the downfall of communication via dating apps has occurred throughout the process. Problem such as trust issue, love scam and online sexual harassment have been experienced by the dating apps users. This research brings the aim of exploring the quality of relationship among youth couples either while using the dating apps or meeting face to face and understanding how the dating apps could bring either positive or negative impacts towards the romantic relationship. The qualitative method used for this research will be in-depth interview whereas purposive sampling will be the method of selecting the interviewees. The findings that have been retrieved from this research, as a whole there are 4 themes which are criteria, critical thinking, communication and relationship. Each of the themes contains different sub-themes. The sub-themes for criteria are appearance, trust, and connectivity whereby the sub-themes for critical thinking are decision making and mutual understanding. Adding on, the sub-themes for communication are preference of communication method, communication barrier and display of emotions while the sub-themes for relationship are appreciation and comfortable.